CD4+ T Cells Mediate the Development of Liver Fibrosis in High Fat Diet-Induced NAFLD in Humanized Mice - Her, Zhisheng; Tan, Joel Heng Loong; Lim, Yee-Siang; Tan, Sue Yee; Chan, Xue Ying; Tan, Wilson Wei Sheng; Liu, Min; Yong, Kylie Su Mei; Lai, Fritz; Ceccarello, Erica; Zheng, Zhiqiang; Fan, Yong; et al. (Frontiers in Immunology, 2020)
Non-alcoholic fatty liver disease (NAFLD) has been on a global rise. While animal models have rendered valuable insights to the pathogenesis of NAFLD, discrepancy with patient data still exists. Since non-alcoholic steatohepatitis (NASH) involves chronic inflammation, and CD4+ T cell infiltration of the liver is characteristic of NASH patients, we established and characterized a humanized mouse model to identify human-specific immune response(s) associated with NAFLD progression. Immunodeficient mice engrafted with human immune cells (HIL mice) were fed with high fat and high calorie (HFHC) or chow diet for 20 weeks. Liver histology and immune profile of HIL mice were analyzed and compared with patient data. HIL mice on HFHC diet developed steatosis, inflammation and fibrosis of the liver. Human CD4+ central and effector memory T cells increased within the liver and in the peripheral blood of our HIL mice, accompanied by marked upregulation of pro-inflammatory cytokines (IL-17A and IFNγ). In vivo depletion of human CD4+ T cells in HIL mice reduced liver inflammation and fibrosis, but not steatosis. Our results highlight CD4+ memory T cell subsets as important drivers of NAFLD progression from steatosis to fibrosis and provides a humanized mouse model for pre-clinical evaluation of potential therapeutics.